Aliran-Aliran pada Periode Krisis dalam Filsafat Matematika: Sebuah Kajian Teori (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
One of the complex thought in terms of issues regarding the foundation and knowledge of mathematics we can call the philosophy of mathematics. The philosophy of mathematics has both coherent and conceptual properties. By having these two characteristics, the philosophy of mathematics has functions that are ordered and directed to the basic concepts they have. Mathematical philosophy has several periods, one of which is the crisis period. In this crisis period, there are schools of philosophy that need to be studied. So this article discusses the currents in the crisis period in the philosophy of mathematics.
Keywords: streams; crisis period; philosophy of mathematics